RURAL POPULATION DYNAMICS IN THE CURVATURE CARPATHIANS - DANIELA VIOLETA NANCU (Revue Roumaine de Géographie)
This over 10,000 km2 sector numbers 800,000 inhabitants, 271 villages grouped into 19 communes and urban centres (18 municipia and towns). The greatest habitat potential have the intra-montane depressions which concentrate approximately two-thirds of the villages in the region, most of them medium-sized demographically with 500–2,000 inhabitants each. Urban population represents 59%, rural population 41%. This geographical area has been inhabited since the Palaeolithic and the Musterian (60,000 – 40,000 BC) a period that made the transition to the Neolithic Times. The analysis of the numerical evolution throughout the rural Curvature Carpathians covers one hundred years (1910–2011) and is based on census data. At communal level, the study focusses on two major periods: communist (1966–1989), when the demographic evolution was rather fluctuating and post-communist (1990–2011), when numbers were mostly on the decline. The analysis of population dynamics has focussed largely on major component elements like the natural and territorial movement which are of primary importance in estimating the demographic vitality of any geographical space.